Penanaman Mangrove di Lagoi Bintan sebagai Upaya Perlindungan Wilayah Pesisir - Tiolina Evi; Kumala, Ratih; Wuri Septi Handayani; Meifida Ilyas (Edujavare Publishing, 2023)
Mangrove forests are one of the most comfortable places for several types of living creatures. This service aims to strengthen the protection of coastal area ecosystems and restore mangrove forest habitat in the country. This service method uses the Participatory Rural Appraisal (PRA) Model which is used in community service activities, prioritizing community empowerment to participate in Mangrove planting activities in Lagoi Bintan. This activity is a collaboration of the peak event of national mangrove planting activities simultaneously in 370 locations in 37 provinces in Indonesia and is carried out in two main series, namely the direct opening via Vicon (Video Conference) by the President of the Republic of Indonesia Ir. H. Joko Widodo (Jokowi) was then followed by planting mangroves simultaneously by all activity participants. The result of this service is that the national mangrove planting program has had a measurable positive impact in mitigating the risk of natural damage and developing the local economy throughout Indonesia, especially the Lagoi Bintan area. It is hoped that it can be an example of how environmental preservation can go hand in hand with sustainable development, preserving natural resources while improving community welfare. So, planting mangroves in Lagoi Bintan is not only an environmental conservation effort, but also a strategic step to improve the economic welfare of the local community.